Relationship of sleep quality with screen-based sedentary time and physical activity in adolescents — the moderating effect of body mass index - Damato, Tatiana M. [UNESP] (2022)
Objective: To analyze the association of sleep quality with reported screen-based sedentary time and reported physical activity, among overweight adolescents. Methods: Adolescents aged 10 to 17 years enrolled in public and private schools were included. Data collection was carried out during the school semesters of 2014–2015 and participants who did not participate in all evaluations were excluded. Sleep quality and physical activity were assessed by validated questionnaires. Screen-based sedentary time was assessed by self-reported mean daily hours spent on television, computer, smartphone/tablet, and videogames. Body mass index was objectively measured and adolescents were classified into normal weight and overweight according to cutoff points for age and sex. Multiple linear regression models adjusted by covariates (age, sex, ethnicity, and socioeconomic status) were used to analyze the relationship between variables. Results: A total of 1008 adolescents were assessed, with a mean age of 13.2 ± 2.4 years and a mean body mass index of 20.4 ± 4.3 kg/m2. Overweight was observed in 28.0% of sample, while 53.0% reported non-white ethnicity. Self-reported screen-based sedentary time was significantly related to poor sleep quality in adolescents (β = 0.116, p = 0.005), remaining significant only in those who were normal weight (β = 0.101, p = 0.007) in sensitivity analysis. Self-reported physical activity showed no relationship with sleep quality in both normal weight and overweight adolescents. Conclusion: Self-reported screen-based sedentary time was associated with poor sleep quality in adolescents, mainly among those with normal weight. The time spent on screen-based sedentary activities can impair sleep quality even in normal weight adolescents.